Analysis of Influencing Factors and Mechanism of Strength of Cement-Modified Silty Sand. (1st November 2021) - Jin, Weidong; Wang, Zhe; Ai, Yongming; Liu, Chenyang
Abstract : The unconfined compressive strength of cement-modified silty sand in Jilin Province was investigated in this study. For this purpose, various tests were conducted, including the screening test, compaction test, CBR test, X-ray fluorescence detection, and unconfined compressive strength test. Effects of compaction degree, soil quality, water quality, cement content, and curing age were considered. The results show that CBR value is positively correlated with compactness. Two kinds of different water qualities have little effect on unconfined compressive strength of cement-improved soil; with the increase in cement content, the unconfined compressive strength increases, and the power function equation established by the two is significantly correlated. The logarithmic relationship between cement-soil strength and curing age is approximately linear. Through regression analysis, the comprehensive characterization parameters of cement-soil strength, such as water-cement ratio, cement content, and curing age, are put forward. The unconfined compressive strength of cement-modified silty sand has a good power function relationship with the comprehensive characterization parameters, and the fitting degree between the strength prediction formula and the existing research and test data exceeds 90%, which verifies the effectiveness of the comprehensive characterization parameters.